2006
DOI: 10.1111/j.1472-765x.2006.01975.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, virulence characteristics and antimicrobial resistance of Escherichia coli O157 in slaughtered cattle and diarrhoeic calves in West Bengal, India

Abstract: Aims:  (i) To study the occurrence of Escherichia coli serotype O157 in cattle stool in West Bengal, India, and (ii) the virulence properties and antimicrobial resistance of the E. coli isolates. Methods and Results:  Following enrichment in modified EC broth and plating onto HiCrome MS.O157 agar, a total of 14 strains of E. coli serotype O157 was isolated from faecal samples from two (2.04%) slaughtered cattle and six (7.59%) diarrhoeic calves. By multiplex PCR, Shiga toxin genes were detected in all the isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 22 publications
5
34
3
Order By: Relevance
“…In this presented study, STEC O157 was detected in 3.3% of 540 cattle rectal swab samples. In comparison with the studies conducted in Turkey and in other countries, this rate is higher than the findings of some researchers 12,27,29,31 and lower than the findings of others 11,13,28,30 . This may result from the differences in seasons, ages of animals, method of breeding and geographic differences.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In this presented study, STEC O157 was detected in 3.3% of 540 cattle rectal swab samples. In comparison with the studies conducted in Turkey and in other countries, this rate is higher than the findings of some researchers 12,27,29,31 and lower than the findings of others 11,13,28,30 . This may result from the differences in seasons, ages of animals, method of breeding and geographic differences.…”
Section: Discussioncontrasting
confidence: 49%
“…In the studies conducted in several countries for determining STEC O157 prevalence in cattle faecal samples, 28 reported detection of the bacterium in 7.2% of the cattle slaughtered in slaughter houses in Bangladesh, Manna et al 29 in 2% of cattle slaughtered in slaughter houses in India, Sasaki et al 30 in 8.9% of beef cattle in Japan, and Zhou et al 31 in 1.7% of cattle faeces in China. In studies conducted in several regions of Turkey, it is reported that E. coli O157 was detected in cattle faeces with rates varying between 0.6% and 25% [10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Within similar geographical locations, a few studies of the occurrence of STEC have been done, and most of the studies were done in India and Thailand (Leelaporn et al, 2003;Manna et al, 2006). Recently, a study was done in central Vietnam that found a prevalence of STEC of 27% in buffaloes, 23% in cattle, and 38.5% in goats.…”
Section: Prevalence Of Shiga-toxin Producing E Colimentioning
confidence: 99%
“…Recently, a study was done in central Vietnam that found a prevalence of STEC of 27% in buffaloes, 23% in cattle, and 38.5% in goats. In India, Manna et al, (2006) reported that the prevalence of STEC O157 in fecal samples from slaughtered cattle and diarrheic calves was 2.0% and 7.6%, respectively (Manna et al, 2006). STEC O157 has also been isolated in India from foods of cattle origin namely raw minced beef samples (9%; n=22) (Dutta et al, 2000), beef surface swabs (3.7%; n=27), and milk samples (2.4%; n=81) (Manna et al, 2006).…”
Section: Prevalence Of Shiga-toxin Producing E Colimentioning
confidence: 99%
See 1 more Smart Citation